Peningkatan Hasil Belajar Siswa Melalui Pembelajaran Berbasis Proyek Di Kelas III Sekolah Dasar - Luluk Mufidah; Punaji Setyosari; Eka Pramono Adi (Edcomtech: Jurnal Kajian Teknologi Pendidikan, 2017)
Improving Student Learning Outcomes through Project-Based Learning in Class III Elementary Schools. This study aims to analyze the application of project-based learning models to improve student learning outcomes and student learning activities. This Classroom Action Research (CAR) was carried out in two cycles using four stages, including: the planning stage, the implementation stage, the observation and reflection stages. The research instrument used was the observation sheet for student learning activities, the observation sheet for teacher teaching activities, tests, and documentation. The results showed that student learning outcomes and student learning activities in class III had increased.